Reconstruction of Participatory Development Paradigm Based on Spiritual Principles for Improving the Social Welfare of Rural Communities (Global Journal of Human-Social Science, 2024)
This study aims to develop a participatory development strategy based on IESQ Power in Konawe Selatan District Government of Indonesia Therefore the research process uses a participatory paradigm in the form of shallow and deep participation and creative participation to improve the welfare of rural communities The result of research showed that the strategic formulation of participatory development based on IESQ Power is a synthetic process between the participatory development cycle with the six Pillars of Faith and five Pillars of Islam Meanwhile the construction of integrated rural development reflects the synergistic process between the participatory development paradigm and religious values which are cored in IESQ Power and Revelation System Thus the use of the participatory development paradigm is not only integrated and interdependent between structural cultural and spiritual approaches however the process of implementing participatory development in rural communities can also take place comprehensively and strategically and be carried out with a full sense of responsibility In turn however it can also be a driving force for social worship that can increase internal motivation for actors in empowerment and other development programs
Keywords: reconstruction; paradigm; participatory development; spirituality; welfare; rural communities